Analisis kinerja Komisi Kode Etik Polri: Sebuah kajian literatur - Sulaiman, Anthonio Effan; Kusumastuti, Retno (Universitas Merdeka Malang, 2023)
Any violation of the professional code of ethics committed by members of the National Police must be accounted for by each member through the National Police Professional Code of Ethics Commission (KKEP). This study aims to analyze the performance of the Police KKEP and the optimization of the performance of the Police KKEP in enforcing the police professional code of ethics. This research uses a qualitative method and literature study approach. analysis using Bibliometric techniques through Vos Viewer software to determine the extent to which the concept of optimizing organizational performance is the topic of research and provides an overview of the performance of the KKEP and the strategies that need to be done to optimize the performance of the KKEP. The results show that the presence of KKEP in overcoming ethical violations is very necessary. One of them is through a model of improving the performance of the professional code of ethics commission based on a literature review base adopted through a capacity building approach integrated with the concept of knowledge management, so that the KKEP Commission can optimally enforce the professional code of ethics for members who commit violations